2021
DOI: 10.21837/pm.v19i16.954
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Factors of Involvement Among Youth to Paddy Field Activities in Homestay Programmes

Abstract: The homestay programme is a community-based tourism that offers tourists to experience the local lifestyle and heritage culture. Many studies focused on challenges of homestay programme, place attachment of hosts, contribution of homestay programme to rural economy. However, very few studies have focused on youths’ involvement in homestay activities. This paper aims to examine the youth’s involvement in homestay activities. A focus group discussion was conducted among the youth aged 20 - 34 years old. A non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…An example is the involvement of youth in homestay activities in Malaysia. Samsudin et al's (2021) study found that the youth in Homestay Kampung D' Belimbing have vast opportunities to contribute to homestay development; however, the elders rarely accept youths' views and continue using their existing ideas and strategies to manage the homestay programme. The issue of trust has led elderly villagers to ignore youths' potential and capabilities in presenting innovative ideas.…”
Section: Innovationmentioning
confidence: 94%
“…An example is the involvement of youth in homestay activities in Malaysia. Samsudin et al's (2021) study found that the youth in Homestay Kampung D' Belimbing have vast opportunities to contribute to homestay development; however, the elders rarely accept youths' views and continue using their existing ideas and strategies to manage the homestay programme. The issue of trust has led elderly villagers to ignore youths' potential and capabilities in presenting innovative ideas.…”
Section: Innovationmentioning
confidence: 94%